Re Lear in città: un exemplum del «Ludus scaccorum» di Iacopo da Cessole nel contesto (Tubach 965) (Carte Romanze, 2024)
The last chapter of the third treatise of Iacopo da Cessole’s Ludus scaccorum is devoted to the city’s marginals (squanderers, gamblers, and couriers). The first exemplum in this chapter is a combination of two very fortunate themes: the ingratitude of sons toward their father and the supposed treasure. This analysis of the exemplum that considers the context in which it is placed allows us to bring out Iacopo’s original use of it: the resolute condemnation of squanderers, a social category irreducible to the common good, eliminates the more obvious and widespread moralization of filial piety toward parents and also the traditional theme of the ingenious joke.